Articulation, Profit or Loss and OCI in the IASB Conceptual Framework: Different Shades of Clean (or Dirty) Surplus. (4th May 2018) - van Mourik, Carien; Katsuo Asami, Yuko
Abstract: The 2015 International Accounting Standards Board (IASB) Conceptual Framework Exposure Draft (2015 IASB CF ED) proposes a mixed valuation and transactions approach to income determination. Nevertheless, it does not clearly choose between single or dual concepts of profit, which renders the 2015 IASB CF ED's financial accounting model somewhat incoherent. The 2015 IASB CF ED proposes a rebuttable presumption that profit or loss should be all-inclusive. Only the IASB can rebut this presumption, but the 2015 IASB CF ED provides no clear conceptual basis on which to rebut this presumption. In spite of considering dual measurement, the IASB believes that it is neither possible, nor necessary, to distinguish between profit or loss and other comprehensive income (OCI) on a conceptual basis. This paper suggests that the 2015 IASB CF ED's approach to measurement can be improved by introducing a deprival value measurement rule in cases where fair value and historical cost are not appropriate. Furthermore, it argues that under dual measurement it is both necessary and possible to make a conceptual distinction between the realised items of income and expense in profit or loss and those recognised by accretion in OCI.